PER UNA METODOLOGIA DELL’INSEGNAMENTO (DELLE LINGUE STRANIERE) - Khakimov M.R (Galaxy International Interdisciplinary Research Journal, 2021)
Mirzo Ulugbek carved on the facade of the university, which he founded in Bukhara and Samarkand, the legend of the Prophet Muhammad: "Man or woman, every Muslim must study science", and to this day in every corner of our world participation in the perception of the magic word associated with the empirical method and experiment of science. One of these words is methodology, magic art (the Latin root of the word magister, namely magis) and therefore there is ambiguity when applying the study of a foreign language.